The Role Of Early Maladaptive Schemas And Coping Strategies In Substance Dependence - Bikem HACIÖMEROĞLU; Mehmet AK; Beyazit GARİP; Alper ÇINAR; Emel CONGOLOĞLU (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi, 2014)
Objective: The aim of this study was to evaluate the early maladaptive schemas and coping strategies of substance dependents. We hypothesized that substance dependents would have more maladaptive schemas and would use less adaptive coping strategies than healthy controls. Methods: Thirty-two patients diagnosed with substance dependence and 31 control subjects without any psychiatric disorders were evaluated via Young Schema Questionnaire-SF, COPE, and Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I). Results: The substance dependents scored significantly higher than the control group in nine out of fourteen early maladaptive schemas. In terms of coping strategies, the substance dependents scored significantly lower than the control group in positive reinterpretation and growth, seeking social support for instrumental reasons, active coping, and seeking social support for emotional reasons, and significantly higher in behavioral disengagement and alcohol-drug disengagement subscales. Moreover, alcohol-drug disengagement type of coping style was significantly predicted by schemas of emotional deprivation, emotional inhibition, enmeshment/dependence, entitlement/ insufficient self-control, abandonment/instability, punitiveness, defectiveness/shame, vulnerability to harm or illness, and unrelenting standards/hypercriticalness. Discussion: Current study showed that the substance dependents had more maladaptive unhealthy core beliefs and ineffective coping strategies than a non-clinical control group. These findings support the importance of early maladaptive schemas which might be the underlying factor for the dependence problem, and might prevent the person to deal with the problem with more active and problem focused coping strategies.